Sustainable Territorial Management - David Rodr´ıguez-Rodr´ıguez (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Human development has made remarkable social and economic progress possible for most of us but has also entailed a range of serious impacts on natural resources, local communities and the economy at multiple scales. Thus, achieving sustainable territorial management that combines healthy and prosperous societies with the long-term maintenance of biodiversity and productive ecosystem services remains the biggest challenge of our modern world. This Special Issue seeks to collect a coherent set of studies on techniques and experiences (case studies) aimed at increasing the environmental, social, economic &/or institutional sustainability of landscapes and seascapes from a range of geographic and socioeconomic contexts. Ten case studies representing urban areas, rural areas (chiefly protected areas) and coastal areas from four countries in Europe and Asia by internationally renowned authors are shown.